Analisis Program Keselamatan dan Kesehatan Kerja (K3) serta Pengaruh terhadap Keberhasilan Proyek Pembangunan Gedung PT. Petrokimia Gresik - Zulma, Nabillah; Dewita, Hikma; Sembiring, Kristina (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2025)
The Occupational Safety and Health (K3) program is very important in implementing building projects. The possibility of work-related accidents and illnesses is often caused by the contractor's failure to implement the program (K3) as intended. A project can be said to be successful if there are no serious accidents or zero accidents. When implementing a building project, it is important to utilize an effective safety and health management system during construction (SMK3). The aim of this research is to understand SMK3 procedures, determine the impact of implementing SMK3, and determine the main factors that influence the success of PT projects. Petrokimia Gresik regarding building construction. This research is quantitative research using two methods, namely assessment based on Key Performance Indicators (KPI) and data analysis using the multiple linear regression method. The data collection method was through distributing questionnaires and the instrument used was a Likert scale. After conducting an assessment based on the Key Performance Indicator (KPI), the implementation of SMK3 in the PT building construction project. Petrochemicals are in line with targets. Furthermore, the research results show that the influence of occupational safety and health (K3) has a positive impact on achieving PT project objectives. Petrochemicals are affected by safety and health issues which have an impact on better implementation of SMK3. The dominant factor that influences project success based on the variables studied is occupational health.